2021
DOI: 10.3390/ani11082236
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Nutritional Metabolism in Transition Dairy Goats: Energy Balance, Liver Activity, and Insulin Resistance in Response to Berberine Supplementation

Abstract: The objectives of this study were to evaluate the alleviating effects of the isoquinoline alkaloid berberine (BBR) on the energy balance (EB), glucose and insulin metabolism, and liver functionality in transition dairy goats, as reflected by blood metabolites and enzymes. Twenty-four primiparous Saanen goats were randomly allocated to four groups. Goats in each group received, ad libitum, the same basal diet during the pre- and post-partum periods of evaluation. Goats received daily0, 1, 2, or 4 g BBR (coded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 65 publications
5
15
0
Order By: Relevance
“…In agreement with current findings, our recent report using the same animal cohort [21] revealed that BBR ingestion in transition goats enhanced pre-and post-partum intakes of DM and NEL. Likewise, it has been reported that BBR enhances energy homeostasis via AMP-activated protein kinase (AMPK) activation [16,[38][39][40].…”
Section: Dry Matter Intake Body Condition Score and Energy Balancesupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with current findings, our recent report using the same animal cohort [21] revealed that BBR ingestion in transition goats enhanced pre-and post-partum intakes of DM and NEL. Likewise, it has been reported that BBR enhances energy homeostasis via AMP-activated protein kinase (AMPK) activation [16,[38][39][40].…”
Section: Dry Matter Intake Body Condition Score and Energy Balancesupporting
confidence: 93%
“…This article is part of a larger study that evaluated the effects of BBR supplementing on performance, glucose metabolism, insulin sensitivity, inflammation, and oxidative stress status in periparturient dairy goats. Our companion paper [21] revealed that BBR ameliorates the NEB in transition goats. The objective of the preset study was to reassess BBR supplementation as a novel preventive approach towards boosting antioxidant indicators in blood and milk, as well as its effects on FA profile in the colostrum and milk of goats during the transition period.…”
Section: Introductionmentioning
confidence: 87%
“…Taken together, the aim of the present study was to determine the effect of BBR supplementation on glucose metabolism and somatotropic axis in dairy goats during late gestation and early lactation. Previous findings within this project confirmed that the BBR-fed does showed improvement in the energy balance (EB) around preparturition period [ 18 ]. Therefore, the hypothesis of this study was that BBR ingestion during the transition from late pregnancy to early lactation, affects glucose metabolism and IR as well as the somatotropic axis.…”
Section: Introductionsupporting
confidence: 77%
“…In a companion study, we observed that BBR supplementation led to reduction in body fat reserve mobilization as indicated by the lower NEFA and BHBA circulation as well as enhanced energy balance (EB) with faster recovery during the first 3 wk. PP [ 18 ]. Therefore, the central aim of present study was to clarify whether the favorable EB of BBR-supplemented dairy goats during transition state was related to enhancement of the regulation in somatotropic axis and glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The lower NEFA concentration in BBR2-and BBR4-fed goats may relate to BBR effects on improvement of energy status and reduction of body reserve usage. Likely, our previous finding (39) suggests that BBR may suppress lipolysis through enhancing feed intake and the endocrine responses that follow in periparturient dairy goats. In support of our findings, Shi et al (41) showed that BBR can improve NEFA-induced lipid accumulation in a dose-dependent manner in bovine hepatocytes.…”
Section: Biomarkers Of Energy Metabolismsupporting
confidence: 56%